TRAILs - Ausbildungsprogramm für angehende und aktuelle Fachfremdsprachenlehrende – Ziele, Durchführung und Evaluation: Ziele, Durchführung und Evaluation. - Woźniak, Joanna; Kic-Drgas, Joanna; Cullen, Joseph; Holloway, Greg (Acta Neophilologica, 2022)
Increasing interest in learning languages for specific purposes, resulting primarily from the growing need for communication in the professional field, has contributed to the expansion of the offer of various language courses for specific purposes at universities and colleges. The international TRAILs project is being carried out to investigate the state of specialist language teaching in European higher education and to prepare and implement methods to develop the competences of language for specific purposes teachers. The aim of this article is to present activities undertaken within the TRAILs project in order to standardise the manner of training for LSP teachers.